2005
DOI: 10.1123/jsm.19.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated Career Satisfaction, Affective Occupational Commitment, and Intentions to Enter the Sport Management Profession

Abstract: The purpose of this study was to examine the impact of internships on students’ career-related affect and intentions. Data were gathered from 138 upper-level undergraduate sport management students (71 interns, 67 noninterns). A doubly multivariate repeated measures model indicated that, although they did not differ at the beginning of the internship, interns had less positive attitudes toward the profession than did noninterns at the end of the internship. Structural equation modeling indicated that affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…The selected students are the closest focus group to professional sport managers that was available because internships indicate a likely successful entering to the career in question (Cunningham et al, 2005). The low number of raters was the result of a low number of students of the MA program that fulfilled the three conditions of: 1) having the aspiration in becoming a sport manager of an elite football club; 2) having already accomplished an internship at one of the targeted clubs; and 3) having experience in computer and video games, especially in the FIFA Manager franchise.…”
Section: Rating Strategymentioning
confidence: 99%
“…The selected students are the closest focus group to professional sport managers that was available because internships indicate a likely successful entering to the career in question (Cunningham et al, 2005). The low number of raters was the result of a low number of students of the MA program that fulfilled the three conditions of: 1) having the aspiration in becoming a sport manager of an elite football club; 2) having already accomplished an internship at one of the targeted clubs; and 3) having experience in computer and video games, especially in the FIFA Manager franchise.…”
Section: Rating Strategymentioning
confidence: 99%
“…However, researchers have not been able to establish a definitive empirical link between diversity and performance in groups (Milliken & Martins, 1996), because investigations into the direct relationship between the two have produced variable results. Some existing studies have shown that diversity can produce negative effects on performance (e.g., Ancona & Caldwell, 1992), while other studies have demonstrated that diverse groups can outperform homogenous groups (e.g., Cunningham & Sagas, 2004;Cox, Lobel, & McLeod, 1991). Despite these mixed results in studies of diversity and performance, a number of management and diversity scholars have attempted to shed light on the importance of diversity in the workplace since the advantages of diversity far outweigh the disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the benefits of diversity are now considered to be one of the most important and influential factors for the success of a sport organization. This belief is primarily due to the evidence that it is related to increases in team performance (Cunningham & Sagas, 2004), enhanced creativity (McLeod, Lobel, & Cox, 1996), and a deep satisfaction found among diverse individuals (Jayne & Dipboye, 2004). With the clear potential for such positive effects, many sport organizations have begun to actively recruit diverse members to their organization and to create an atmosphere that celebrates diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Sports studies using the occupational affective scale with other occupational variables have also found positive correlations with job satisfaction (Pack, 2005) and career satisfaction (Cunningham, Sagas, Dixon, Kent, & Turner 2005) and a negative correlation with turnover intentions (Turner & Chelladurai, 2005). The findings have important implications for organizations seeking to keep employees satisfied while reducing job-related hiring and retention costs (Turner & Chelladurai, 2005).…”
Section: Technological Linkagesmentioning
confidence: 94%
“…The findings have important implications for organizations seeking to keep employees satisfied while reducing job-related hiring and retention costs (Turner & Chelladurai, 2005). Researchers have examined the construct with various occupational groups such as university athletic administrators (Pack, 2005;Turner & Chelladurai, 2005), fitness club employees (Chang & Chelladurai, 2003), and sport administration college interns (Cunningham, Sagas, Dixon, Kent, & Turner, 2005).…”
Section: Technological Linkagesmentioning
confidence: 99%